KESIAPSIAGAAN BENCANA: LANGKAH PENTING UNTUK MENGURANGI RISIKO - Putri Hasanah Harahap; Yesa Dwi Khairani; Iga Nailah Aulia Br Lubis; Usiono (Cahaya Ilmu Bangsa Institute, 2025)
This research aims at the importance of disaster preparedness to reduce risk. This research emphasizes the importance of collaboration between government, local communities and related institutions in building disaster resilience. This research examines important steps in disaster preparedness, including public education, risk mapping, preparing emergency plans, strengthening infrastructure, and using technology for early warning systems. This research method uses a qualitative method with a library research approach. Disaster preparedness is a strategic effort that aims to reduce the impact of disasters on humans, the environment and assets. Indonesia, as a country that is vulnerable to various types of natural disasters such as earthquakes, floods and volcanic eruptions, requires a holistic approach to increase the preparedness of society and government.Keywords: Preparedness, Disaster, Risk